Distribution of microorganisms in soil horizon at different depths of in Al Jabal Al Akhdar - Alhassan, Gadalla A.; Maleh, Abdulkader; FEDEEL, Gazzalla I (Al-Mukhtar Journal of Sciences, 1992)
This study was conducted to evalu ate the distribution of microscopic or- ganisms which include: bacteria, fungi, actinomycetes and nematodes in the soil profile at different depths in El-gebel Alakhder area. The present study indicated that all microscopic organisms decreased with the increase of soil depth, except Tylen- chus spp., Helicotylenchus spp. and Par- atylenchus spp.. There was a significant difference in the distribution of microscopic organi- sms within the different depths in the soil profile. It was shown that most mi- croscopic organisms concentrated at the depth of (0-40 cm.)